1998
DOI: 10.7326/0003-4819-129-12-199812150-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Genetic Differences in Omeprazole Metabolism on Cure Rates for Helicobacter pylori Infection and Peptic Ulcer

Abstract: The results of the genotyping test for CYP2C19 seem to predict cure of H. pylori infection and peptic ulcer in patients who receive dual therapy with omeprazole and amoxicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
243
5
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(268 citation statements)
references
References 15 publications
10
243
5
10
Order By: Relevance
“…An important implication of the identification of highly variable CYP2D6 activity is that new drug candidates that are eliminated predominantly by this enzyme are often not further developed (23,24). In contrast to CYP2D6, the poor metabolizer trait for a different CYP, CYP2C19, is more common in Asian persons, and persons with this genotype have higher drug concentrations and a greater cure rate of Helicobacter pylori infections during therapy with the CYP2C19 substrate omeprazole (25).…”
Section: Coding-region Variantsmentioning
confidence: 99%
“…An important implication of the identification of highly variable CYP2D6 activity is that new drug candidates that are eliminated predominantly by this enzyme are often not further developed (23,24). In contrast to CYP2D6, the poor metabolizer trait for a different CYP, CYP2C19, is more common in Asian persons, and persons with this genotype have higher drug concentrations and a greater cure rate of Helicobacter pylori infections during therapy with the CYP2C19 substrate omeprazole (25).…”
Section: Coding-region Variantsmentioning
confidence: 99%
“…Moreover, the same authors could also demonstrate the significance of CYP2C19 genotype for eradication upon dual therapy (amoxicillin as the only antibiotic and high doses of omeprazole) showing cure rates of 100% in PMs. 79 For that reason, the authors concluded that in Japanese patients homozygous for CYP2C19 defect alleles, the dual therapy might be sufficient. Furuta et al 80 also suggested that CYP2C19 genotyping test could be a useful tool for deciding on the optimal treatment regimen with PPIs, including a dual (PPI plus antibiotic) or a triple (PPI plus two antibiotics) therapy.…”
Section: Ulcer Disease and Proton Pump Inhibitorsmentioning
confidence: 99%
“…Based on a series of cellular, animal and human studies, we now realize that both intestinal metabolic enzymes and efflux transporters, working together as a protective mechanism, may be responsible for the poor bioavailability of a number of drugs (Furuta T, 1998;Schellens JH, 2000;Luo FR, 2002). Drug metabolizing enzymes and drug-transporters critically regulate the extent of drug distribution throughout the body and the rate of drug clearance from the body (Volm M, 1991;Wacher VJ, 1995).…”
Section: Drug Metabolizing Enzymes and Drug-transportersmentioning
confidence: 99%
“…Omeprazole, a drug used to treat gastroesophageal reflux disease, is both a substrate and an inhibitor of CYP2C19. As a result, individuals with reduced CYP2C19-mediated activity will suffer from impaired clopidogrel bioactivation and enhanced accumulation of omeprazole (Furuta et al, 1998;Li et al, 2004;Roden et al, 2009). …”
Section: Drug Disposition: Effects Age Sex and Ethnicitymentioning
confidence: 99%